Pengucapan Ikrar Talak Tanpa Kehadiran Istri Di Pengadilan Agama - Muhammad Juhasa Jamaludin; La Ode Angga; Syadzwina Hindun Nabila (LUTUR Law Journal, 2024)
Divorce Case No. 326/Pdt.G/2022/PA.AB in which the Respondent (Wife) has been properly and officially summoned by the court, but the Respondent (Wife) never attended and did not send her attorney to represent her in the trial process until the Declaration of Divorce by the Applicant (Husband), however, the panel of judges still allowed the Applicant (Husband) to pronounce the Declaration of Divorce after the verdict of the Divorce case was issued, then a Divorce Certificate was issued which clearly explained the condition of the Respondent (Wife) at the time of the Declaration of Divorce. based on the Compilation of Islamic Law (KHI) Article 149 is obliged to provide maintenance to the Respondent (his wife), or at least the Respondent (his wife) must be present to ask for maintenance in accordance with KHI Article 119 Paragraph 2 Letter b, and other things that need to be considered by the panel of judges as always stated in the Divorce Certificate, namely, seeing the status of the wife in a state of purity, menstruation or in a state of pregnancy or not at the time the divorce vow was pronounced according to Article 122 of the KHI. The type of research used in this study is normative juridical. The results of this study are that according to Islamic law, the applicant in the divorce case of the divorce vow number 326 / Pdt.G / 2022 / PA.AB has met the requirements required in Islamic law to pronounce the divorce vow. However, because the wife was not present in the trial, the judge should not have fulfilled the legal requirements to allow the applicant to pronounce the divorce vow because Article 119 Paragraph 2 of the KHI point b regarding the divorce vow with ransom or khuluk (iddah and mut'ah maintenance) and the wife's condition which must be stated in the divorce certificate according to Article 122 of the KHI have not been fulfilled, so that the pronouncement of the divorce vow in the case is considered invalid according to law. That in order to protect the wife's rights legally and ensure the wife's condition as an additional requirement for the validity of the divorce certificate, the wife's presence in court is a significant factor for the court in carrying out its legal process fairly and ensuring that the decision taken not only takes into account the provisions of religious law, but also takes into account aspects of humanity and social justice.